Constraint reasoning for differential models - Cruz, Jorge (Frontiers in artificial intelligence and applications, 2005)
Focuses on the integration of ordinary differential equations within the interval constraints framework, which for this purpose is extended with the formalism of Constraint Satisfaction Differential Problems. Such a framework allows the specification of ordinary differential equations by means of constraints.